1971
DOI: 10.1111/j.1432-1033.1971.tb01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Ethanolamine Pyrophosphate during Mild Acid Hydrolysis of the Lipopolysaccharide of Pseudomonas aeruginosa

Abstract: Low molecular weight solutes released during mild acid hydrolysis of the lipopolysaccharide of Pseudornonas aeruginosa were isolated from the fraction containing the partially degraded polysaccharide, by successive chromatography on columns of Sephadex G-75 and G-10, followed (as necessary) by preparative high voltage paper electrophoresis. The major components identified were 2-keto-3-deoxyoctonic acid, basic amino acids (free and bound), inorganic orthophosphate, ethanolamine phosphate and ethanolamine pyrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…A much higher phosphate content, up to 10 or more phosphate groups, has been reported for LPS of P. aeruginosa, and most of them are considered to be located in the core region [12–14], although some phosphate may be present as triphosphate residues [13]. On mild acid hydrolysis, much of the phosphate can be released as P i , PP i and ethanolamine mono‐, di‐ and triphosphates [42,43]. No more phosphate groups could be retained in the core after alkaline degradation of the LPS of P. aeruginosa [10] as di‐ and triphosphates are unstable under alkaline conditions as well (P. M. Sánchez Carballo et al, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…A much higher phosphate content, up to 10 or more phosphate groups, has been reported for LPS of P. aeruginosa, and most of them are considered to be located in the core region [12–14], although some phosphate may be present as triphosphate residues [13]. On mild acid hydrolysis, much of the phosphate can be released as P i , PP i and ethanolamine mono‐, di‐ and triphosphates [42,43]. No more phosphate groups could be retained in the core after alkaline degradation of the LPS of P. aeruginosa [10] as di‐ and triphosphates are unstable under alkaline conditions as well (P. M. Sánchez Carballo et al, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…The LPS may include up to 10 phosphate groups, most of which are located in the core region. Some phosphate may occur as di‐ and tri‐phosphate residues [19,32,34] and be substituted with ethanolamine [34–36]. The LPS of P. aeruginosa 2192 studied in this work contained monophosphate and diphosphate groups, but no significant amounts of triphosphate groups or ethanolamine (data of 31 P‐ and 1 H‐NMR spectroscopy).…”
Section: Discussionmentioning
confidence: 97%
“…Earlier studies by Newton (16) demonstrated that Mg"4 and polymyxin B competed for a P. aeruginosa cellular site, which he postulated to be polyphosphate in nature. P. aeruginosa LPS has been demonstrated to have an especially high phosphate concentration (5) and may have at least 8 mol of phosphate per mol of LPS in the heptose-2-keto-3-deoxyoctonate region (A. Kropinski, personal communication). Since phosphoryl and phosphodiester groups are negatively charged at neutral pH, this high-phosphate region of the LPS would provide binding sites for Mg2", thus explaining the relatively high Mg"4 content of P. aeruginosa cell envelopes (2).…”
Section: Discussionmentioning
confidence: 99%